Voces de los actores (Diálogos críticos en educación: voces y experiencias., 2024)
David Arellano GaulLuis Montaño HiroseJosé Alfredo Zavaleta BetancourtLaura Zamudio GonzálezRebeca Elizabeth Contreras LópezRubén Darío Jiménez RosadoIrma Alicia García Contreras